Identifcation and control potential of entomopathogenic nematodes against the black cutworm, Agrotis ipsilon (Fabricius) (Lepidoptera: Noctuidae), in potato‑growing areas of Turkey - Gümüş Askar, Arife; Yüksel, Ebubekir; Ocal, Atilla; Özer, Göksel; Kutuk, Halil; Dababat, Abdelfattah A.; Imren, Mustafa (Springer, 2022)
The black cutworm (BCW), Agrotis ipsilon (Hufnagel, 1766) (Lepidoptera: Noctuidae), is one of the major pests of potato, and its outbreaks frequently occur in potato-growing areas of Turkey. Entomopathogenic nematodes (EPNs) in the families of Steinernematidae and Heterorhabditidae are known as an important biocontrol agent to many insects including BCW. In 2020 and 2021, surveys of EPNs were conducted in major potato-growing areas of seven provinces of Turkey, including Afyonkarahisar, Konya, İzmir, Sivas, Bolu, Kayseri, and Niğde, in the sake to find a new sustainable biological control option for BCW. Out of the 400 collected soil samples, 48 samples (12%) consisted of EPNs. Based on the morphological, morphometric, and sequence analysis of the internal transcribed spacer (ITS), 34 isolates were identified as Steinernema feltiae Filipjev, 1934 (Rhabditida: Steinernematidae), 13 isolates as Heterorhabditis bacteriophora Poinar, 1976 (Rhabditida: Heterorhabditidae), 1 one isolate as Oscheius tipulae Lam and Webster, 1971 (Rhabditida: Rhabditidae). The virulence of EPN isolates was assessed on the larvae of Galleria mellonella L. (Lepidoptera: Pyralidae), and the most pathogenic isolates were further tested for their biocontrol potential against the 3rd/4th larval instar of BCW larvae at two concentrations of 50 and 100 IJs/cm2 under laboratory conditions. All selected isolates were highly effective against the larvae of BCW, and larval mortality ranged between 70 and 100% for both concentrations after 3 days of exposure time. The maximum mortality (100%) was achieved only by two isolates (H. bacteriophora AF-12 and S. feltiae KAY-4) at the higher concentration of 100 IJs/cm2. The results indicate that EPNs are abundantly present in potato-growing areas of Turkey and have the potential to be used in the biocontrol of BCW. To our knowledge, this is the first report of the presence of Oscheius tipulae in Turkey.